COVID-19 and the UK Biobank—Opportunities and Challenges for Research and Collaboration With Other Large Population Studies - Khanji, Mohammed Y.; Aung, Nay; Chahal, C. Anwar A.; Petersen, Steffen E. (Frontiers in Cardiovascular Medicine, 2020)
Large population studies such as the UK Biobank provide great opportunities for understanding the pathophysiology, health impact and prognostic factors associated with COVID-19, a condition that has had significant impact on almost everyone around the world. We highlight the vast opportunities, challenges and limitations for research and collaboration from the UK Biobank and other large population studies in helping us better understand and manage both current and potential future pandemics.